PENGEMBANGAN E-MODUL GARIS DASAR UNTUK SISWA FASE E TATA BUSANA SMK - Kaffa, Fissilmi; Arifiana, Deny; Nahari, Inty; Yuniati, Mita (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2024)
Electronic module (E-Module) is one of the media that can be used by teachers to help achieve effectiveness and efficiency in the learning process. The purpose of this research is to determine the feasibility of the E-module media for the application of basic lines, to understand students' responses after the E-module has been implemented, and to assess the results of the basic lines application practice after using the E-module. This research is a research and development (R&D) study using the ADDIE development model. The research subjects are 35 students from the Fashion Design Phase-E at SMK Negeri 1 Sooko Mojokerto. The data collection methods used were questionnaires and assessment tests. The results of the research on the application of the E-Module media received a very good category with an average score of 95%, student responses received a very good category with an average score of 81%, and the results of the basic line application practice after using the E-Module received a complete category with an average score of 83.43%. Based on the research findings, it can be concluded that the E-Module for students of SMK Negeri 1 Sooko Mojokerto is very suitable and beneficial for both teachers and students